Peningkatan Mutu Pendidikan Madrasah Diniyah melalui Partisipasi Masyarakat - Jannah, Miftahul; Diana, Eka (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This study aims to improve the quality of education in Madrasah Diniyah Ar-rozaq through increasing community participation. The community here significantly influences the ongoing education process in an early institution environment. Schools can survive and develop to show the surrounding community a high awareness of the importance of diniyah education. This research was conducted using a qualitative case study method with the research location in Bucor Kulon Village. The results obtained are: community participation in Madrasah Diniyah Arrozaq is outstanding and quality. Madrasah Diniyah Ar-rozaq, when viewed at the level of input, process, and output, is also quite good. Then the role of community participation in improving the quality of this madrasah at least provides supervision in the form of criticism, suggestions, and input in determining the curriculum. All levels of society there want to send their children to madrasah diniyah because it is based on awareness of the importance of religious education in this era of globalization. They also participate in any activities.